Coding Accuracy Analysis Of Ina-Cbg’s Cause Of Negative Claims at Dr. Moewardi Hospital - Yeni Tri Utami; Nabilatul Fanny; Devi Pramita Sari (LPPM Universitas Duta Bangsa Surakarta, 2021)
The difference in rates between the real costs and the INA-CBG package rates is one of the causes of the decline in service revenues at the hospital, one of which is in Dr. Moewardi as a type A hospital in the Surakarta area. In Tribulan 1 2020, there were 2680 differences in negative claims. One of the cases that caused a high negative difference was the obgyn case with Cesarean Section action, namely 73 files which caused a negative difference of IDR-361,971,358. The accuracy of the diagnostic code can affect and cause differences in the INA-CBGs rates. The purpose of this study was to analyze the accuracy of the Cbgs Ina code the cause of negative claims in Dr. Moewardi. The method in this research is descriptive research with a cross sectional approach, namely examining the data directly at the time of the study. The study population was the BPJS claim file in the 1st quarter of 2020 which had a negative difference of 2680 files. The sample in this study used a sampling technique with a purposive sampling method with the criteria for the inclusion of a claim file that had a negative difference between obgyn cases and Cesarean Section action with the code Ina Cbgs (O-6-11-I, O-6-11-II, O- 6-11-III) and negative claim file exclusion criteria with obgyn cases not using Cesarean Section measures and negative claims files with non-obgyn cases. The number of samples was 73 files. Analysis of the accuracy of the diagnosis code and action in this Cesarean Section case is interpreted as a percentage. The results showed that the correct code was 71.23% compared to the incorrect percentage of 28.77%. The highest category of inaccuracy in the diagnosis code was due to the secondary diagnosis that was not coded by 42.86%, and the lowest was wrong in determining the primary diagnosis by 4.76%. Of the 28.76% (21 documents) that were not fast, only 2 files differed between hospital fees and researchers which caused a negative difference of Rp. 2,559,500. Conclusion Based on the results of the study, the accuracy of the obsgyn case diagnosis code by section action was greater than the incorrect one. Not all of the incorrect code causes the difference in the amount of the difference in negative claims.